Efeito de diferentes tempos de exposição a um ambiente enriquecido na memória de camundongos : uma abordagem comportamental e molecular - Rohor, Bruna Zanetti (2015)
The environment is formed by a set of situations around the individual and has influence on all organisms. A stressor environment has negative influences in a subject, but an enriched environment (EE) has positive influences. In animals, the AE is defined as a combination of inanimate and social complex stimuli that can improve motor, cognitive and sensory functions. The EE is composed of different objects of different shapes, sizes, colors, textures, among others. Environmental novelty, voluntary physical activity and social interaction are also part of EE. The EE is capable of promoting increased visual, sensory, cognitive and motor functions. Cognitive improvement, increased synaptic plasticity, adult hippocampal neurogenesis, modulation of gene expression and changes in levels of neurotransmitters and neurotrophic factors are EE-induced alterations already described. However, several EE paradigms are found in the literature, and this variety of protocols produces a range of controversial results on the effects induced by EE.